Impact of tropical Pacific variability on the mean North Atlantic thermohaline circulation - Semenov, Vladimir; Latif, Mojib (Geophysical Research Letters, 2006)
A series of 500 years long coupled general circulation model simulations has been performed, in which the sea surface temperatures (SSTs) in different tropical oceans have been prescribed from climatology. A statistically significant reduction by about one Sverdrup of the meridional overturning circulation (MOC) in the North Atlantic was found when the tropical Pacific SSTs do not vary interannually. Anomalously low salinities originating in the tropical Atlantic due to increased precipitation drive the reduction of the MOC. Climatological SSTs in the tropical Pacific lead to a “La Niña”-like state due to the nonlinear response of the atmosphere to SST anomalies. The shift of the mean atmospheric circulation in the tropical Pacific leads to a cyclonic anomaly over the eastern tropical Atlantic with a corresponding precipitation increase. The results suggest that changes in the SST variability of the tropical Pacific can drive changes in the mean state of remote regions.